Calcifying Epithelial Odontogenic Tumor (Clear-Cell Variant) A case report and literature review - A. Hamouda, Saleh; M. Musa, Asma; ElHoni, Ashour; M. Elmurtadi, Ali (Libyan Journal of Dentistry, 2017)
Calcifying epithelial odontogenic tumor (CEOT), or the Pindborg tumor, is very rare neoplasm, which accounts up to 1% of all odontogenic tumors. CEOT is locally aggressive benign odontogenic neoplasm arising from epithelial tissue. CEOT is rarely reported in Libya. Here in, we present an additional case of 55 year old female patient with a clear cell Variant (CCEOT) of CEOT located in the left posterior maxilla with maxillary sinus extension, with an emphasis on clinical, radiographic and histopathology features and review of literatures.